Impact of Entrepreneurial Identity Aspiration and Self-Efficacy towards Entrepreneurial Behavior of the Working Class of Davao City - Daisy Vale Avila de Gracia; Karl P. Campos (Program Studi Pendidikan Ekonomi Fakultas Keguruan dan Ilmu Pendidikan Universitas Lambung Mangkurat, Banjarmasin, 2023)
The objective of this research is to quantify the relationship of Entrepreneurial Identity Aspiration and Self-Efficacy to Entrepreneurial Behavior of the working class of Davao City, Philippines where the culture has strong emphasis on working and providing for the family. The data is collected from 150 working people in Davao City through the e-questionnaires using Snowball sampling. Using a correlation-descriptive research design and multiple linear regression technique, the study's findings indicate that the desire for an entrepreneurial identity and one's self- efficacy have a notable influence on engaging in entrepreneurial actions. However, the study also identified that Self-efficacy has a higher correlation and effect towards Entrepreneurial Behavior. Furthermore, the results on Entrepreneurial Identity Aspiration show different results compared to relative studies presented. The results assume that even with the desire and aspiration to take an entrepreneurial role in the future, a person who is lacking on self-efficacy will not engage on entrepreneurial activities.